Handbook of Stressful Transitions Across the Lifespan - Miller, Thomas W.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The modern life cycle is characterized by stressful transitions, when unexpected events$1 (Band even many expected ones$1 (Bchallenge people$1 (Bs functioning, health, and sense of self-worth. The international, multidisciplinary perspectives provided in the Handbook of Stressful Transitions Across the Lifespan cover these periods as they occur through youth, adulthood, and aging, bringing together theoretical and clinical findings, case studies, and literature reviews in one authoritative volume. A diverse panel of clinicians, researchers, and educators focuses on the psychological, biological, cultural and spiritual factors surrounding not only trauma and loss but also coping and growth, risk and mitigating factors, and promising interventions. Whether topics are just beginning to receive in-depth attention (the first job; becoming adoptive parents), ongoing issues requiring new insights (veterans$1 (Badjustment to civilian life; chronic illness), or emerging concepts (trauma growth; animal-assisted therapy), coverage is well-written, engaging, and eminently useful. A sampling of the topics featured in the Handbook: The developmental neurobiology of stress. The long-term effects of divorce on children. Self-regulation across life transitions. Money in (E)motion: stressful financial transitions. The influence of food on adapting to life stressors. The transition to retirement as a stressful event. With its comprehensive scope and wealth of data, the Handbook of Stressful Transitions Across the Lifespan will appeal to a variety of professional readers, including researchers and scholars in the fields of social, developmental and clinical psychology, sociology, and public health.s
Processing Transitions in the Life Span -- Life Stress and Transitions in the Life Span -- Life Transitions and Stress in the Context of Psychosocial Development -- The Neurobiology of Stress Throughout the Life Cycle -- Life as a Source of Theory: Erik Erikson$1 (Bs Contributions, Boundaries, and Marginalities -- Education and Career Transitions -- College-to-Workplace Transitions: Becoming a Freshman Again -- Coping with Job Transitions over the Work Life -- Transitioning into Retirement as a Stressful Life Event -- Marriage, Family and Sexual Life Cycle Transitions -- Family Transitions Following Natural and Terrorist Disaster: Hurricane Hugo and the September 11 Terrorist Attack -- The Transition to Adoptive Parenthood -- Transitioning the Impact of Divorce on Children Throughout the Life Cycle -- Stress, Mindful Parenting, and the Transition to Adulthood -- Sexual Transitions in the Lives of Adult Women -- Family and Spousal Adaptation to Transitioning a Traumatic Event -- Legal, Ethical and Financial Transitions -- Ethical and Legal Issues in Transitioning the Lifespan -- Money in (E)Motion Experienced in Stressful Financial Transitions -- Dual Cognitive Processes and Alcohol and Drug Misuse in Transitioning Adolesence -- Life Threatening Transitions in Maturation and Health -- Life Stress and Managing Transitions Unanticipated Change of Course: The Diagnosis of Chronic Progressive Neurological Disease: No Deal! -- Transitions Throughout the Cancer Experience: Diagnosis, Treatment, Survivorship, and End of Life -- Loss of the Safety Signal in Childhood and Adolescent Trauma -- An Unexpected Traumatic Change in Life: Where to Go from Here? -- The Role of Self-Awareness and Communication in Issues of Health and Aging -- Cultural, Religious, and Spiritual Influences in Life's Transitions -- Self-Regulation Across Some Life Transitions -- Time, Culture, and Life-Cycle Changes of Social Goals -- Refugees$1 (BLife Transitions from Displacement to Durable Resettlement -- Religious Worldviews and Stressful Encounters: Reciprocal Influence from a Meaning-Making Perspective -- Life Stress Buffer: The Salubrious Role of African-Centered Spirituality -- Directions and Interventions in Stressful Life Transitions -- Surviving and Thriving: How Transition Psychology May Apply to Mass Traumas and Changes -- Posttraumatic Growth: A Positive Consequence of Trauma -- Psychological Impact of Genetic Testing -- Functional Fitness, Life Stress, and Transitions Across the Life Span -- Nutrition Through the Life Span: Needs and Health Concerns in Critical Periods -- The Role of Animals and Animal-Assisted Therapy in Stressful Life Transitions -- The Role of Humor in Transforming Stressful Life Events -- Concluding Comments and Future Considerations for Stressful Life Events and Transitions Across the Life Span.s
Keywords: Philosophy (General).; Sociology; Developmental psychology; Psychology; Developmental Psychology; Sociology; Public Health/Gesundheitswesen.